Female Fertility Has a Negative Relationship With Longevity in Chinese Oldest-Old Population: A Cross-Sectional Study - Zhu, Qiao; Fu, Shihui; Zhang, Qian; Tian, Jinwen; Zhao, Yali; Yao, Yao (Frontiers in Endocrinology, 2021)
Background Despite research efforts in this field for more than a century, the relationship between female fertility and longevity is unclear. This study was designed to investigate this relationship in Chinese oldest-old population. Methods The China Hainan Centenarian Cohort Study was performed in 18 cities and counties of Hainan. A total of 1,226 females, including 758 centenarian women and 468 women aged 80–99 years, were enrolled in this study. Using a standardized protocol, in-person interviews and blood analyses were conducted by a well-trained research team through home visits. Results Centenarian women had significantly lower number of children (NOC) and higher initial childbearing age (ICA) and last childbearing age (LCA) than women aged 80–99 years (p < 0.05 for all). Multivariate logistic regression analysis showed that NOC and testosterone (T) levels were positively associated with women aged 80–99 years, when centenarian women was considered as reference (p < 0.05 for all). ICA, LCA, and estradiol (E2) levels were negatively associated with women aged 80–99 years, when centenarian women was considered as reference (p < 0.05 for all). Conclusions The centenarians had crucial characteristics of less and delayed childbearing, indicating a negative relationship between female fertility and longevity in Chinese oldest-old population. Serum E2 levels were positively associated and serum T levels were negatively associated with longevity. The less and late childbearing might be a significant factor of longevity, and successful aging might be promoted by reducing and delaying female childbearing.